Mediating Effects of Adolescent Physical Activity, Self-Rated Health and Family Income - Wang, Meng; Shen, Xi; Deng, Lamei; Yu, Feng; Lou, Yin; Liu, JunJi; Huang, Yibing (Frontiers in Public Health, 2022)
Objective To investigate and analyse the situation and relationship between adolescent physical activity and self-assessment of health to provide a reference for adolescent physical activity research. Methods A questionnaire was used to investigate the physical activity and self-rated health of 1,804 adolescents aged 14–18 years. Results There was a significant relationship between adolescents' physical activity and self-rated health. The coefficient was 0.109 (P < 0.01) in urban areas and 0.127 (P < 0.01) in rural areas. At the same time, it was found that when family income was used as the intermediary variable between physical activity and self-rated health, the intermediary effect was 0.12 (P < 0.01), and the intermediary effect accounted for 25.97%. Conclusion Adolescent obesity, physical activity, smoking, wellbeing and physical activity can affect adolescents' self-rated health status. At the same time, it is also found that adolescents' family income is an intermediary variable between physical activity and self-rated health. Suggestions (1) Increase the methods of sports venues, sports organizations and sports activities, improve the possibility of teenagers participating in physical activities, and improve teenagers' self-rated health; (2) There is a large gap between the physical activity and self-rated health of urban and rural adolescents. Increasing the guidance of physical activity of adolescents in rural areas promotes the balance of self-rated health of urban and rural adolescents. (3) Family income is the intermediary variable of teenagers' physical activities and self-rated health. Reducing family expenditure through financial transfer payments or reducing taxes and fees can increase the level of teenagers' physical and mental health.